2012
DOI: 10.1186/1756-0500-5-120
|View full text |Cite
|
Sign up to set email alerts
|

Conserved requirement for DEAD-box RNA helicase Gemin3 in Drosophila oogenesis

Abstract: BackgroundDEAD-box RNA helicase Gemin3 is an essential protein since its deficiency is lethal in both vertebrates and invertebrates. In addition to playing a role in transcriptional regulation and RNA silencing, as a core member of the SMN (survival of motor neurons) complex, Gemin3 is required for the biogenesis of spliceosomal snRNPs (small nuclear ribonucleoproteins), and axonal mRNA metabolism. Studies in the mouse and C. elegans revealed that loss of Gemin3 function has a negative impact on ovarian physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
3
7
1
Order By: Relevance
“…Consistent with the well-documented role of RNA helicases in oogenesis and fertility (87,(123)(124)(125)(126), we identified two putative DEAD-box helicases, CG10077 and Mahe (Maheshvara). While CG10077 is an ortholog of human DDX5, Mahe is an evolutionary conserved regulator of Notch signaling (127).…”
Section: Identification Of Novel Genes With a Potential Role In Drososupporting
confidence: 83%
“…Consistent with the well-documented role of RNA helicases in oogenesis and fertility (87,(123)(124)(125)(126), we identified two putative DEAD-box helicases, CG10077 and Mahe (Maheshvara). While CG10077 is an ortholog of human DDX5, Mahe is an evolutionary conserved regulator of Notch signaling (127).…”
Section: Identification Of Novel Genes With a Potential Role In Drososupporting
confidence: 83%
“…In contrast to other DEAD box proteins that have been directly implicated in Drosophila oogenesis (Cauchi, 2012;Johnstone et al, 2005;Styhler et al, 1998;Tomancak et al, 1998), we propose that the infertility observed in Ddx1 null females is due to disrupted metabolism. Altered metabolism also provides a possible explanation for the small number of progeny generated by Ddx1 AX /Df (3L)ED230 females, as we observed slightly higher pS6k levels and slightly larger body size in these mutants compared to the completely sterile Ddx1 AX/AX females.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, defects in the U2-snRNP component noisette produce a range of oogenic defects depending on the severity of the allele, including novel abnormal condensation of NC nuclei, delayed development, sensory bristle growth, and fertility [57]. Mutations in SMN also produce NCCD defects in the female germ line, which also suggest that impaired snRNP assembly may be a factor in the NCCD phenotype; the RNA-helicase Gemin 3 also co-localizes with SMN and retains NCCD failure in the mutant germ line as well [58], [59]. Therefore, defects in spliceosome integrity/dynamics can have dramatic effects on multiple aspects of development.…”
Section: Discussionmentioning
confidence: 99%